A new Suggested Conjugate Gradient Algorithm with Logistic Mapping - Omar, Dlovan H. (Science Journal of University of Zakho, 2016)
In this paper, we will use logistic mapping to find new conjugate gradient coefficients for unconstrained optimization.
Keywords: Unconstrained Optimization; Conjugate Gradient Method; Logistic Mapping